2012
DOI: 10.3126/njenthns.v2i2.6793
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Profile of Chronic Supurative Otitis Media

Abstract: Nepalese Journal of ENT Head and Neck Surgery Vol.2 No.2 Issue 2 (July-Dec 2011) 6-7 DOI: http://dx.doi.org/10.3126/njenthns.v2i2.6793

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
24
1
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 5 publications
17
24
1
4
Order By: Relevance
“…A total of 55 (22.9%) patients of the total OM cases were found in this age group. Previous study done by Ahmad and Kudi, 15 Shrestha et al, 3 Jha et al 16 and dissertation conducted by Koppad 10 also found similar result. It was in contrast to the study done by Raakhee et al, where the prevalence was in age group of 16-25 years.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…A total of 55 (22.9%) patients of the total OM cases were found in this age group. Previous study done by Ahmad and Kudi, 15 Shrestha et al, 3 Jha et al 16 and dissertation conducted by Koppad 10 also found similar result. It was in contrast to the study done by Raakhee et al, where the prevalence was in age group of 16-25 years.…”
Section: Discussionsupporting
confidence: 78%
“…Among the isolates, Staphylococcus aureus (36.11%) was found to be the most predominant organism followed by Pseudomonas aeruginosa 39%). The result is also in harmony with the study done by Shrestha et al, 3 Kristo and Buljan, 8 Ayson et al 23 and Nia et al 24 The frequency of Staphylococcus aureus in middle ear infections can be attributed to their ubiquitous nature and high carriage of resistant strains in the external auditory canal and upper respiratory tract. 25 The second most common organism isolated was Pseudomonas aeruginosa (33.33%).…”
supporting
confidence: 79%
See 1 more Smart Citation
“…S, Janardhan Rao R 10 and V. K. Poorey and Arati lyer, 8 showing younger patients presenting more with the disease. Females dominated the number in this study, comparable to the study conducted in Nepal by Shrestha BL et al, 14 but contradictory findings were seen in the study of V. K. Poorey and Arati lyer 8 and Harvinder Kumar, Sonia Seth 11 in which males' outnumbered females. The study was conducted on 150cases from which 198 bacterial and fungal isolates were procured.…”
Section: Observations and Resultssupporting
confidence: 61%
“…11 Our study has shown that Pseudomonas aeruginosa (38%) and Staphylococcus aureus (23.15%) are the major pathogen involved in the etiology of CSOM, which is at par with some other studies. [7][8][9]12 The isolates showed maximum sensitivity to piperacillin (41%) and levofloxacin (41%). Sensitivity to amikacin and netilmicin were seen in 36% of isolates.…”
Section: Discussionmentioning
confidence: 99%